Co-Creating Healthcare Campaigns through Design and Social Marketing Approaches - Coutinho Da Silva; Silvio Augusto Minciotti, Edson (British Journal of Marketing Studies, 2022)
This theoretical article aims to present and describe the role of the design thinking approach, and social marketing canvas model in designing and improving an action plan for a healthcare campaign addressed to target audiences exposed to a disease, such as COVID-19. The latest global events encouraged this author to produce and write this essay to introduce two agile instruments for co-creating and co-producing a healthcare campaign considering the citizen experience. The design approach and social marketing canvas are based on agile methodologies and lean principles to reach two primary results: (a) design, co-create and co-produce a ’social product/service’; (b) social marketing canvas co-organises the strategies required to address the ’social product/service’ to a target audience. Furthermore, both tools have the role of inducing a social change by policymaking in healthcare campaigns in a humanised way and considering the individuals as the primary agents of social change. Citation: Edson Coutinho Da Silva and Silvio Augusto Minciotti (2022) Co-Creating Healthcare Campaigns through Design and Social Marketing Approaches, British Journal of Marketing Studies, Vol. 10, Issue 1, pp.1-12